"Put Yourself in Their Shoes": Testing Empathy's Ability to Motivate Cosmopolitan Behavior. Issue 1 (2nd March 2017) - Faulkner, Nicholas
Abstract : Political theorists have long contemplated the concept of cosmopolitanism, yet almost no empirical studies have investigated how individuals can be encouraged to act as ethical cosmopolitans in practice. This article reports the findings of an experiment designed to investigate the effect of empathy on cosmopolitan‐helping behavior. The extent to which empathy may be useful in motivating cosmopolitan behavior has been the subject of substantial debate among political theorists. Empathy was manipulated using a perspective‐taking technique adapted from social psychological research, and the extent to which individuals were willing to engage in cosmopolitan helping was measured. Results showed that perspective taking increased cosmopolitan helping and that empathy mediated that effect. Furthermore, empathy was found to predict cosmopolitan helping even after controlling for several related constructs. Overall, results indicate that increasing empathy by encouraging people to take the perspective of distant individuals is a promising way to foster cosmopolitan helping.